INCOME, MENTAL HEALTH, AND STANDARD OF LIVING: A MALAYSIAN PERSPECTIVE - Costa Dara Krishna, Lingeh (Universiti Malaysia Sarawak (UNIMAS), 2022)
The general objective of this study is to determine the general objective of study is to investigate the relationship between income, mental health, and standard of living from the perspective of citizens in Malaysia. In this study, the primary data was used with 386 respondents who are Malaysian citizens that will be analyzed using Statistical Package For The Social Science (SPSS) software. The test used to determine the result of this study consists of Kendall's tau-b test, Spearmen's rho test, and the ordinal regression. This study found that there is a strong relationship between income and standard of living where the household income, income sufficiency in covering needs, meeting everyday income expenses and financial satisfaction have significant results. Hence, mental health also shows it has an inverse relationship with the standard of living where the depression average has a negative value of correlation coefficient. Therefore, the Malaysian government needs to implement and introduce new ways and solutions in increasing the standard of living in contribute towards economic growth by focusing on income and mental health status.